2020
DOI: 10.32598/irj.18.3.949.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Online Dialogic Storytelling on Vocabulary Skills of Hard of Hearing Children

Abstract: Objectives: The present study aimed to investigate the effectiveness of an online dialogic storytelling program on vocabulary skills (picture, relative, and oral vocabulary skills) of hard of hearing children. Methods: In this experimental study with pre-test-post-test and a control group design, 34 mothers of hard of hearing children participated. Children’s ages range from 4 to 6 years and they were selected from aural rehabilitation centers in Tehran. They were assigned randomly into the experimental (n=17)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…In their study, Rezaiyan et al demonstrated that hard-of-hearing children's vocabulary, picture comprehension, and oral vocabulary skills improved significantly after participating in online dialogic storytelling sessions. This research reaffirms the effectiveness of dialogue-based methods, including mother-child dialogic storytelling of hard-of-hearing children [20].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In their study, Rezaiyan et al demonstrated that hard-of-hearing children's vocabulary, picture comprehension, and oral vocabulary skills improved significantly after participating in online dialogic storytelling sessions. This research reaffirms the effectiveness of dialogue-based methods, including mother-child dialogic storytelling of hard-of-hearing children [20].…”
Section: Discussionsupporting
confidence: 70%
“…Although we could not find similar studies to the present research, some studies investigated the effectiveness of early interventions, including book reading and storytelling programs, on children in preschool and school ages. Among them, we can mention the studies conducted by Greenhut and Beyer [6], Rezaiyan et al [20], and Kaderavek et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…The deaf and hard-of-hearing (DHH) child or adolescent in a family may affect all family members [3]. Deafness puts a person in a difficult place [4], while relationships with family members and DHH peers provide endless opportunities to learn how to resolve interpersonal, emotional, and social problems [5].…”
Section: Introductionmentioning
confidence: 99%